√2+√5-√32=
3√48-5√3-2√27=
√3(√27+4√3)=
√2(2√2+√72)=
(√3+2)²-√12=
(√45-√5)²-20=
De calculat va rog ajutatima
Răspunsuri la întrebare
Răspuns de
1
√2+√5-√32=√2+√5-4√2=-3√2+√5
3√48-5√3-2√27=3•4√3-5√3-2•3√3=12√3-5√3-6√3=√3
√3(√27+4√3)=√3(3√3+4√3)=√3•7√3=7•3=21
√2(2√2+√72)=√2(2√2+6√2)=√2•8√2=8•2=16
(√3+2)^2-√12=(√3)^2+2•√3•2+2^2+2√3=3+4√3+4+2√3=7+6√3
(√45-√5)^2-20=(3√5-√5)^2-20=(2√5)^2-20=20-20=0
3√48-5√3-2√27=3•4√3-5√3-2•3√3=12√3-5√3-6√3=√3
√3(√27+4√3)=√3(3√3+4√3)=√3•7√3=7•3=21
√2(2√2+√72)=√2(2√2+6√2)=√2•8√2=8•2=16
(√3+2)^2-√12=(√3)^2+2•√3•2+2^2+2√3=3+4√3+4+2√3=7+6√3
(√45-√5)^2-20=(3√5-√5)^2-20=(2√5)^2-20=20-20=0
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă